Enhancing EFL Students’ Speaking Performance through Digital Storytelling: A Quasi-Experimental Study at Mts. Madani Alauddin Pao-Pao - Nurhasna Basri; Muhammad Tahir; Maemuna Muhayyang (Faculty of Education and Teacher Training of UIN Palopo, 2026)
This study aims to investigate the use of digital storytelling as a learning medium to improve students’ speaking skills. Specifically, it examines whether the implementation of digital storytelling significantly enhances students’ ability to speak English and explores students’ perceptions toward its use in the learning process. This research used a quantitative approach with quasi experimental design. The population of the research was the eighth-grade students. The sample was 20 students as experimental class and 20 students as control class20 students in the experimental class and 20 students in the control class.The researcher used test and questionnaire as the instruments of this research. The researcher used a speaking test and a students’ questionnaire as the instruments of this research. This research analysed the effect of using digital storytelling in improving students’ speaking skills. The design of this research was a quantitative research through quasi experimental using a non-equivalent group design. Quasi experimental in this research to measure the effect of the objects being experimented with. The result showed that the mean score of pre-tests in the experimental class was 51.8, and in the control class was 52.4. and the mean score of the experimental class in the post-test was 66.5, and the control class was 58.61. There was a significant effect of the mean score between the two groups on students’ speaking skills in using digital storytelling, but not in MTs Madani Alauddin Pao-pao. Questionnaire responses were analysed descriptively to determine the mean score of 4.075 shows that students’ attitude in the affective component belongs to the Positive category. The study concluded that the use of digital storytelling has a positive impact on students' speaking skills at MTs Madani Alauddin Pao- pao. Students feel more confident, more creative, and can better organise their ideas. Despite challenges in terms of technical skills and the time required to create digital stories, the benefits gained from using digital storytelling are significant in improving students' speaking skills.